Prueba tamizaje de alergias alimenticias (2020)
Allergies appear when the immune system reacts to a foreign substance, be it food, medicine, cosmetic or any foreign substance that may be in contact with the body in some way or another. This substance should not cause a reaction by the immune system in most people. Faced with this reaction, the human body produces antibodies that recognize allergens as harmful, even if they are not. The severity of these allergic reactions varies depending on the person, it can range from minor irritation to anaphylaxis or even death. Although allergies have no cure, they can be mostly treated. For its part, it has been estimated that in Colombia there are more than 2 million children and adolescents in school who are allergic to at least one food. And, in general, allergy diagnostic tests are difficult to access in Colombia. Therefore, we identified the need to carry out an easily accessible food allergy screening test for children between 3 and 18 years old that serves as a public health measure to carry out the food list of schools in Colombia